^{1}

^{*}

^{2}

The purpose of this paper is to study a semilinear Schr
ödinger equation with constraint in
*H*
^{1}(
R
^{N}), and prove the existence of sign changing solution. Under suitable conditions, we obtain a negative solution, a positive solution and a sign changing solution by using variational methods.

This article deals with the following semilinear Schrödinger equation with constraint

{ − Δ u + V ( x ) u = λ f ( x , u ) , x ∈ R N , u ∈ H 1 ( R N ) , ∫ R N ( | ∇ u | 2 + V ( x ) u 2 ) d x = r 2 , u ( x ) → 0, | x | → + ∞ . (1.1)

Given r > 0 , we try to find ( u , λ ) to satisfy the Equation (1.1). We say ( u , λ ) a positive solution if u is positive, a negative solution if u is negative, and a sign changing solution if u is sign changing.

Several authors have considered a Schrödinger equation of the form

{ − Δ u + V ( x ) u = f ( x , u ) , x ∈ R N , u ∈ H 1 ( R N ) , u ( x ) → 0, | x | → + ∞ . (1.2)

In Bartsch and Wang [

Some papers concern with the problem (1.1). Under some conditions, a positive and a negative solution can be found in [

In order to state our results, we require the following assumptions:

(A_{1}) V ∈ L l o c ∞ ( R N ) , inf x ∈ R N V ( x ) > 0 .

(A_{2}) f : R N × R → R is locally Lipschitz continuous, and there are constants C > 0 and p ∈ ( 2, 2 * ) such that

| f ( x , t ) | ≤ C ( 1 + | t | p − 1 ) for x ∈ R N , t ∈ R ,

where 2 * : = 2 N N − 2 for N ≥ 3 and 2 * : = ∞ for N = 1 , 2 . Moreover, f ( x , t ) = o ( | t | ) as t → 0 uniformly in x.

(A_{3}) There is a constant η > 2 such that

0 ≤ η F ( x , t ) ≤ f ( x , t ) t for x ∈ R N , t ∈ R ,

where F ( x , t ) : = ∫ 0 t f ( x , s ) d s for x ∈ R N , t ∈ R .

(A_{4}) There is an open subset Ω ⊂ R N such that t f ( x , t ) > 0 for x ∈ Ω and | t | sufficiently large.

(A_{5}) l i m | x | → + ∞ sup | t | ≤ r | f ( x , t ) | | t | = 0 for every r > 0 .

Our main result is the following theorem.

Theorem 1.1 Suppose (A_{1})-(A_{5}) hold. Then problem (1.1) has at least three nontrivial solutions u + , u − , and u ¯ , where u + is positive, and u − is negative and u ¯ changes sign.

The key point is to construct certain invariant sets of the gradient flow associated with the energy functional of the elliptic problem. All positive and negative solutions are contained in these invariant sets. And minimax procedures can be used to construct sign changing critical point of the energy functional outside these invariant sets.

We first fix some notations. Denote the usual Sobolev space by W m , p ( R N ) , and set H m ( R N ) = W m , 2 ( R N ) . Consider the Hilbert space

H : = { u ∈ H 1 ( R N ) : ∫ R N V ( x ) u 2 d x < + ∞ } .

We introduce the inner product in H by the formula

〈 u , v 〉 : = ∫ R N ( ∇ u ⋅ ∇ v + V ( x ) u v ) d x for u , v ∈ H ,

and the corresponding norm

‖ u ‖ : = 〈 u , u 〉 for u ∈ H .

According to (A_{1}), there is a continuous embedding H ↪ H 1 ( R N ) , hence

H ↪ L s ( R N ) for 2 ≤ s ≤ 2 * . (2.1)

Note that by (A_{2}) for any ε > 0 , there is a constant K 1 ( ε ) > 0 such that

| f ( x , t ) | ≤ ε | t | + K 1 ( ε ) | t | p − 1 for x ∈ R N , t ∈ R . (2.2)

Assumption (A_{3}) implies that given δ > 0 , there exists a constant K 2 ( δ ) > 0 such that

F ( x , t ) ≥ K 2 ( δ ) | t | η − δ | t | 2 for x ∈ R N , t ∈ R . (2.3)

Denote

S r : = { u ∈ H : ∫ R N ( | ∇ u | 2 + V ( x ) u 2 ) d x = r 2 } ,

F ( x , u ) : = ∫ 0 u f ( x , t ) d t for u ∈ R , (2.4)

J ( u ) : = − ∫ R N F ( x , u ) d x for u ∈ H , (2.5)

I : = J | S r . (2.6)

By Zeidler [

I ′ ( u ) = J ′ ( u ) − 〈 J ′ ( u ) , u 〉 ‖ u ‖ 2 u for u ∈ S r , (2.7)

where 〈 J ′ ( u ) , v 〉 = − ∫ R N f ( x , u ) v d x for u , v ∈ H . It is easy to see from (2.7) that the critical points of I correspond to the solutions of problem (1.1) with λ = − ‖ u ‖ 2 〈 J ′ ( u ) , u 〉 . And I is bounded.

Definition 2.1 Suppose E is a real Banach space. For Φ ∈ C 1 ( E , R ) , we say Φ satisfies the Palais-Smale condition (denoted by (PS)) if any sequence { u n } ⊂ E for which { Φ ( u n ) } is bounded and Φ ′ ( u n ) → 0 possesses a convergent subsequence. We say Φ satisfies (PS)_{c} for a fixed c ∈ R if any sequence { u n } ⊂ E for which Φ ( u n ) → c and Φ ′ ( u n ) → 0 possesses a convergent subsequence. We say Φ satisfies (PS)^{+} if Φ satisfies (PS)_{c} for all c > 0 ; Φ satisfies (PS)^{−} if I satisfies (PS)_{c} for all c < 0 .

Lemma 2.1 [^{−}.

Let G be the Nemytskii operator induced by f, the mapping I ′ may be written as

I ′ ( u ) = − T ( u ) u − K G ( u ) for u ∈ S r , (2.8)

where T ( u ) : = − 1 r 2 ∫ R N f ( x , u ) u d x and K : = ( − Δ + V ) − 1 . Note that

K G ( u ) = ( − Δ + V ) − 1 f ( ⋅ , u ( ⋅ ) ) for u ∈ H .

In other words, KG is uniquely determined by the relation

〈 K G ( u ) , v 〉 = ∫ R N f ( x , u ) v d x , for u , v ∈ H . (2.9)

I ′ ( u ) is globally Lipschitz continuous in H applying (A_{2}) [

Let E be a real Banach space, Φ ∈ C 1 ( E , R ) and E ¯ : = { u ∈ E : Φ ′ ( u ) ≠ 0 } . We will give some relevant definitions below.

Definition 2.2 A locally Lipschitz continuous mapping Q : E ¯ → E is called a pseudo-gradient vector field (denoted by p.g.v.f) for Φ on E ¯ if it satisfies the following conditions

1) ‖ Q ( u ) ‖ E ≤ 2 ‖ Φ ′ ( u ) ‖ E * ;

2) 〈 Φ ′ ( u ) , Q ( u ) 〉 E ≥ ‖ Φ ′ ( u ) ‖ E * 2 .

Suppose Q is a p.g.v.f for Φ on E ¯ , and consider the initial value problem in E ¯

{ d d t σ ( t , u ) = − Q ( σ ( t , u ) ) , t ≥ 0 σ ( 0 , u ) = u . (2.10)

According to the theory of ordinary differential equations in Banach space [

Definition 2.3 A nonempty subset M of E is called an invariant set of descending flow for Φ determined by Q if

{ σ ( t , u ) | 0 ≤ t < ω + ( u ) } ⊂ M

for all u ∈ E ¯ ∩ M .

Definition 2.4 Let M and D be invariant sets of descending flow for Φ , D ⊂ M . Denote

C M ( D ) = { u | u ∈ D , or u ∈ M \ D andthereis 0 ≤ t < ω + ( u ) suchthat σ ( t , u ) ∈ D }

If D = C M ( D ) , then D is called a complete invariant set of descending flow relative to M.

In this section we shall recall some results about the flow generated by I ′ . We refer to Mawhin and Willem [

It is clear that I ′ is globally Lipschitz continuous, and I ′ is a p.g.v.f of I. In the following we consider the initial value problem

{ d σ d t = − I ′ ( σ ) = T ( σ ) σ + K G ( σ ) , t ≥ 0 , σ ( 0 , u ) = u , u ∈ S r . (3.1)

Applying the theory of ordinary differential equations, we obtain:

Lemma 3.1 [

σ ( t , u ) = e ∫ 0 t T ( σ ( s , u ) ) d s ( u + ∫ 0 t e − ∫ 0 s T ( σ ( ξ , u ) ) d ξ K G ( σ ( s , u ) ) d s ) . (3.2)

Lemma 3.2 [

In our case, I is bounded and so it follows from Lemma 3.2 that ω + ( u ) = + ∞ for u ∈ S r .

Lemma 3.3 [

It is easy to verify that d ( ‖ σ ‖ 2 ) d t = 0 , that is

σ ( t , u ) ∈ S r for u ∈ S r . (3.3)

In our further proof, we shall need the following Lemma which is derived by Brézis and extended by Martin to infinite dimensional space (cf. Theorem 1.6.3 in [

Lemma 3.4 [

lim h ↓ 0 d i s t E ( u + h Q ( u ) , D ) h = 0 for u ∈ ∂ D . (3.4)

where d i s t E ( . , . ) is the distance on E. If u 0 ∈ D and σ ( t ) with 0 ≤ t < ω + ( u 0 ) is the solution of the initial value problem

{ d σ d t = Q ( σ ) , σ ( 0 , u 0 ) = u 0 ,

then σ ( t ) ∈ D for all t ∈ [ 0, ω + ( u 0 ) ) .

Next we will discuss the convex cones P + : = { u ∈ H : u ≥ 0 } , and P − : = { u ∈ H : u ≤ 0 } . Moreover, for u ∈ H we denote that u + : = max { u , 0 } and u − : = min { u , 0 } . Note that u ∈ H implies u ± ∈ P ± . Consider the sets

P ε + : = { u ∈ H : d i s t ( u , P + ) < ε } , P ε − : = { u ∈ H : d i s t ( u , P − ) < ε } ,

as well as P ε : = P ε + ¯ ∪ P ε − ¯ for ε > 0 . Note that P ε + and P ε − are open convex subsets of H, whereas P ε is a closed and symmetric subset of H. Moreover, H \ P ε contains only sign changing functions.

Note that I ′ is a p.g.v.f for I, we can obtain a flow σ : B → E satisfying (3.1) for all ( t , u ) ∈ B : = { ( t , u ) : u ∈ H ¯ , 0 ≤ t < ω + ( u ) } , where ω + ( u ) ∈ ( 0, + ∞ ] is the maximal existence time for the trajectory σ ( t , u ) . We call σ the descending flow associated with I ′ . A subset M ⊂ H is invariant for the σ if

σ ( t , u ) ∈ M , forevery u ∈ M andevery t ∈ [ 0, ω + ( u ) ) .

If M is an invariant subset of H, we also consider

A ( M ) : = { u ∈ H : σ ( t , u ) ∈ M forsome t ∈ ( 0, ω + ( u ) ) } ,

and in addition we put

A 0 : = { u ∈ H : σ ( t , u ) → 0 as t → ω + ( u ) } .

Note that A 0 is open.

In this section, we will give some proposition for finding three solutions with one changing sign.

Proposition 4.1 Suppose W is a finite dimensional subspace of H, there holds:

1) sup J ( W ) < + ∞ ;

2) If sup J ( C ) < + ∞ , where C : = { t u : t ≥ 0, u ∈ S } and S is a closed subset of some finite dimensional subspace W of H, then there is a constant R > 0 such that

J ( u ) < − 1 2 ‖ u ‖ 2 for u ∈ C \ B R ( 0 ) . (4.1)

Proof. 1) Obviously.

2) If we define

Φ ( u ) : = 1 2 ‖ u ‖ 2 − ∫ R N F ( x , u ( x ) ) d x for x ∈ R N , u ∈ H ,

then

J ( u ) = Φ ( u ) − 1 2 ‖ u ‖ 2 for u ∈ H .

Inequality (2.3) implies that for any δ > 0 there exist constants a 1 , a 2 > 0 , such that

Φ ( u ) ≤ 1 2 ‖ u ‖ 2 − K ( δ ) ∫ R N | u | η d x + δ ∫ R N | u | 2 d x ≤ a 1 ‖ u ‖ 2 − a 2 ‖ u ‖ η .

Hence for R = ( a 1 a 2 ) 1 η − 2 we have

Φ ( u ) < 0 , for u ∈ C \ B R ( 0 ) .

Thus (4.1) hold. □

Using (2.7), we can note that

I ′ ( u ) = u − K G ( u ) T ( u ) = u − A ( u ) for u ∈ S r , (4.2)

where A ( u ) : = K G ( u ) T ( u ) .

Proposition 4.2 There exists ε 0 > 0 such that for 0 < ε ≤ ε 0 , there holds

1) If u ∈ P ε ± ∩ S r and t ∈ [ 0, ω + ( u ) ) , then σ ( t , u ) ∈ i n t ( P ε ± ) ∩ S r ;

2) Every nontrivial solution u ∈ P ε − ∩ S r of (1.1) is negative, and every nontrivial solution u ∈ P ε + ∩ S r of (1.1) is positive.

Proof. 1) Let d : = 1 2 inf x ∈ R N V ( x ) > 0 , u ∈ S r and v = K G ( u ) , then

‖ u + ‖ L 2 = min y ∈ P − ‖ u − y ‖ L 2 ≤ 1 2 d min y ∈ P − ‖ u − y ‖ = 1 2 d d i s t ( u , P − ) .

Similarly, using (2.1) we find for every s ∈ [ 2, 2 * ] , there is a constant C s > 0 with

‖ u ± ‖ L s ≤ C s d i s t ( u , P ∓ ) . (4.3)

Since v − ∈ P − , v − v − = v + ∈ P + , we have

d i s t ( v , P − ) ≤ ‖ v − v − ‖ = ‖ v + ‖ .

It follows from (2.2), (2.9) and (4.3) that

d i s t ( v , P − ) ‖ v + ‖ ≤ ‖ v + ‖ 2 = 〈 v , v + 〉 = 〈 K G ( u ) , v + 〉 = ∫ R N f ( x , u ) v + d x ≤ ∫ R N f ( x , u ) + v + d x = ∫ R N f ( x , u + ) v + d x ≤ ∫ R N ( d | u + | + K ( d ) | u + | p − 1 ) v + d x ≤ d ‖ u + ‖ L 2 ‖ v + ‖ L 2 + K ( d ) ‖ u + ‖ L p p − 1 ‖ v + ‖ L p ≤ ( 1 2 d i s t ( u , P − ) + K ¯ d i s t ( u , P − ) p − 1 ) ‖ v + ‖ ,

with a constant K ¯ > 0 . Hence

d i s t ( v , P − ) ≤ 1 2 d i s t ( u , P − ) + K ¯ d i s t ( u , P − ) p − 1 .

So there exists ε 0 > 0 such that

d i s t ( K G ( u ) , P − ) ≤ 3 4 d i s t ( u , P − )

for every u ∈ P ε − ∩ S r with 0 < ε ≤ ε 0 . Thus

K G ( u ) ∈ i n t ( P ε − ) for u ∈ P ε − ∩ S r . (4.4)

For any u ∈ P ε − , we can choose δ > 0 small enough such that

u + h ( T ( u ) u + K G ( u ) ) = ( 1 + h T ( u ) ) u + h K G ( u ) ∈ P ε − for h ∈ ( 0 , δ )

Thus

lim h ↓ 0 d i s t ( u − h I ′ ( u ) , P ε − ) h = 0 for u ∈ ∂ P ε − . (4.5)

It follows from Lemma 3.4 that if σ ( t , u ) is the solution of (3.1), then it will hold that σ ( t , u ) ∈ P ε − for all t ∈ [ 0, ω + ( u ) ) . So we can obtain from (4.4) that

K G ( σ ( t , u ) ) ∈ i n t ( P ε − ) for u ∈ P ε − ∩ S r , t > 0. (4.6)

Set α ( t ) : = − ∫ 0 t T ( σ ( s , u ) ) d s , then α ′ ( t ) > 0 , α ( t ) > 0 , and α ( t ) is strictly increasing. Applying (4.6), we have

K G ( σ ( t , u ) ) α ′ ( t ) ∈ i n t ( P ε − ) for u ∈ P ε − ∩ S r . (4.7)

If we define B ( t ) : = K G ( σ ( t , u ) ) α ′ ( t ) , and F t : = { B ( s ) : 0 ≤ s ≤ t } , then F t is a compact set of H. According to (4.7), F t ⊂ i n t ( P ε − ) and hence c o ¯ F t ⊂ i n t ( P ε − ) , where c o ¯ F t is the closed convex hull of F t in H. Note that

1 e α ( t ) − 1 ∫ 0 t e α ( s ) K G ( σ ( s , u ) ) d s = 1 e α ( t ) − 1 ∫ 1 e α ( t ) K G ( σ ( α − 1 ( ln s ) , u ) ) α ′ ( α − 1 ( ln s ) ) d s = lim m → + ∞ 1 m ∑ i = 1 m A ( α − 1 ( ln ( 1 + i m ( e α ( t ) − 1 ) ) ) ) ∈ c o ¯ F t ⊂ i n t ( P ε − ) .

From (3.2) we get

σ ( t , u ) = e − α ( t ) u + 1 − e − α ( t ) e α ( t ) − 1 ∫ 0 t e α ( s ) K G ( σ ( s , u ) ) d s . (4.8)

Denote F : = { u , 1 e α ( t ) − 1 ∫ 0 t e α ( s ) K G ( σ ( s , u ) ) d s } , then F is also a compact set of H. Using by (4.6) and (4.8), we obtain that

σ ( t , u ) ∈ c o ¯ F ⊂ i n t ( P ε − ) .

Hence σ ( t , u ) ∈ i n t ( P ε − ) ∩ S r for u ∈ P ε − ∩ S r and t ∈ [ 0, ω + ( u ) ) . And σ ( t , u ) ∈ i n t ( P ε + ) ∩ S r for u ∈ P ε + ∩ S r and t ∈ [ 0, ω + ( u ) ) can be proved analogously.

(2) Put w = − K G ( u ) T ( u ) , it follows from (2.9) that

d i s t ( w , P − ) ‖ w + ‖ ≤ ‖ w + ‖ 2 = 〈 w , w + 〉 = 〈 − K G ( u ) T ( u ) , w + 〉 = r 2 ( ∫ R N f ( x , u ) u d x ) − 1 ∫ R N f ( x , u ) w + d x .

Any u ∈ S r , 1 r 2 ∫ R N f ( x , u ) u d x > 0 . By (2.2) and (4.3), for 0 < ξ < d r 2 ∫ R N f ( x , u ) u d x < K 1 with a constant K 1 > 0 , we get

∫ R N f ( x , u ) w + d x ≤ ∫ R N f ( x , u ) + w + d x = ∫ R N f ( x , u + ) w + d x ≤ ∫ R N ( ξ | u + | + K ( ξ ) | u + | p − 1 ) w + d x ≤ ξ ‖ u + ‖ L 2 ‖ w + ‖ L 2 + K ( ξ ) ‖ u + ‖ L p p − 1 ‖ w + ‖ L p ≤ ( δ 2 d d i s t ( u , P − ) + K 2 d i s t ( u , P − ) p − 1 ) ‖ w + ‖ ,

with a constant K 2 > 0 . So

d i s t ( w , P − ) ‖ w + ‖ ≤ ( 1 2 d i s t ( u , P − ) + K ˜ d i s t ( u , P − ) p − 1 ) ‖ w + ‖ ,

with a constant K ˜ > 0 . Thus

d i s t ( w , P − ) ≤ 1 2 d i s t ( u , P − ) + K ˜ d i s t ( u , P − ) p − 1 .

Hence, for ε 0 > 0 small enough

d i s t ( − K G ( u ) T ( u ) , P − ) ≤ 3 4 d i s t ( u , P − )

for every u ∈ P ε − ∩ S r with 0 < ε < ε 0 . In particular we have A ( ∂ P ε − ) ⊂ P ε − . If moreover u ∈ P ε − satisfies A ( u ) = u , then u ∈ P − . If finally u ≠ 0 , we conclude u ( x ) < 0 for all x by the maximum principle [

In view of Proposition 4.2, the next proposition just follows from Liu and Sun [

Lemma 4.1 [

Lemma 4.2 [

h ( 0 ) ∈ D 1 \ D 2 , h ( 1 ) ∈ D 2 \ D 1 ,

and

inf u ∈ D 1 ¯ ∩ D 2 ¯ Φ ( u ) > inf t ∈ [ 0,1 ] Φ ( h ( t ) ) .

Then Φ has at least four critical points, one in D 1 ∩ D 2 , one in D 1 \ D 2 ¯ , one in D 2 \ D 1 ¯ , and one in E \ ( D 1 ¯ ∪ D 2 ¯ ) .

Note that I ′ is a p.g.v.f of I such that P ε + and P ε − are invariant for the associated descending flow. Moreover

∂ P ε ± ⊂ A ( P ε ± ) for 0 < ε ≤ ε 0 . (4.9)

holds following from Proposition 4.2 and Lemma 4.1.

Proposition 4.3 If 0 < ε ≤ ε 0 , then P ε + ¯ ∩ P ε − ¯ ⊂ A 0 . In particular there holds

J ( u ) > − 1 2 ‖ u ‖ 2 for u ∈ P ε + ¯ ∩ P ε − ¯ \ { 0 } . (4.10)

Proof. First, from (A_{2}) and (A_{3}) we have

∫ R N F ( x , u ) d x ≤ 1 η ∫ R N f ( x , u ) u d x ≤ C η ( ‖ u ‖ L 2 2 + ‖ u ‖ L p p ) .

Since by (3.3) we infer that

‖ u ‖ L s 2 = ‖ u + + u − ‖ L s 2 = ‖ u + ‖ L s 2 + ‖ u − ‖ L s 2 ≤ C s 2 d i s t ( u , P − ) 2 + C s 2 d i s t ( u , P + ) 2 ≤ 2 ε 2 C s 2 .

Hence, for u ∈ P ε + ∩ P ε −

J ( u ) = 1 2 ‖ u ‖ 2 − ∫ R N F ( x , u ) d x − 1 2 ‖ u ‖ 2 ≥ 1 2 ‖ u ‖ 2 − C η ( ‖ u ‖ L 2 2 + ‖ u ‖ L p p ) − 1 2 ‖ u ‖ 2 ≥ 1 2 ‖ u ‖ 2 − C η ( 2 ε 2 C s 2 + ( 2 ε 2 C s 2 ) p 2 ) − 1 2 ‖ u ‖ 2 ≥ − 1 2 ‖ u ‖ 2 .

Next we recall that P ε + ∩ P ε − contains no critical points of I by Proposition 4.2. Thus by (4.9), (4.10) and the invariance of P ε + ∩ P ε − we find that

σ ( t , u ) → 0 as t → ω + ( u )

for every u ∈ P ε + ¯ ∩ P ε − ¯ as claimed. □

As a consequence of the preceding discussion, the existence of three solutions with one changing sign follows from Lemma 4.2.

Proof of Theorem 1.1 Choose v ∈ S r , and set

C : = { t v + + s v − : t ≥ 0, s ≥ 0 } .

It follow from Proposition 1, there exists R > 0 such that

J ( u ) < − 1 2 ‖ u ‖ 2 for u ∈ C \ B R ( 0 ) .

By the choose of r, we have r > R , now we define the path

h : [ 0,1 ] → S r , h ( t ) = t r ‖ v + ‖ v + + ( 1 − t ) r ‖ v − ‖ v − ,

then

h ( 0 ) = r ‖ v − ‖ v − ∈ C ∩ P ε − ∩ S r , h ( 1 ) = r ‖ v + ‖ v + ∈ C ∩ P ε + ∩ S r ,

hence

sup t ∈ [ 0 , 1 ] I ( h ( t ) ) = sup t ∈ [ 0 , 1 ] J ( h ( t ) ) < − r 2 2 .

Applying Proposition 4.3, we obtain

J ( u ) > − 1 2 ‖ u ‖ 2 for u ∈ P ε + ¯ ∩ P ε − ¯ \ { 0 } .

Thus

inf u ∈ P ε + ¯ ∩ P ε − ¯ I ( u ) > − r 2 2 .

So we have

inf u ∈ P ε + ¯ ∩ P ε − ¯ I ( u ) > sup t ∈ [ 0 , 1 ] I ( h ( t ) ) .

Since I satisfies (PS)^{−}, I ′ ( u ) = u − A ( u ) for u ∈ S r , P ε + and P ε − are open convex subsets of H, P ε + ∩ P ε − ∩ S r ≠ ∅ . And by Proposition 4.2, A ( P ε ± ¯ ∩ S r ) ⊂ P ε ± ¯ ∩ S r . It follows from Lemma 4.2 that I has a critical points u + ∈ ( P ε + \ P ε − ) ∩ S r , u − ∈ ( P ε − \ P ε + ) ∩ S r , u ¯ ∈ S r \ ( P ε + ¯ ∪ P ε − ¯ ) , where u + is a positive solution of (1.1), u − is a negative solution of (1.1) and u ¯ is a sign changing solution of (1.1). □

This article is supported by the Science and Technology Project of Fujian Provincial Department of Education (JAT191148).

The authors declare no conflicts of interest regarding the publication of this paper.

Liu, J.K. and Fan, Q. (2021) Sign Changing Solution of a Semilinear Schrödinger Equation with Constraint. Applied Mathematics, 12, 489-499. https://doi.org/10.4236/am.2021.126034